ПРОФЕССИОНАЛ ТӘЛИМНИҢ АБЗАЛЛЫҚЛАРЫ ҲӘМ ЭКОНОМИКАЛЫҚ ТӘРЕПЛЕРИ - Қанглибеков, Қ.Д. (SCIENCE and SOCIETY, 2020)
The article provides an overview of the benefits of vocational education. The importance of professional education in the life of a specialist is closely related to his interests and abilities. It was noted that the problem of unemployment in our society is the result of a lack of cooperation between the employer and institutions of secondary specialized education.
Keywords: professional education; profession; interest; ability; economics; unemployment problem; employer